COGITA network has constructed a glossary of diagnostic reasoning terms. (2nd October 2017) - Barais, Marie; Hauswaldt, Johannes; Dinant, Geert-Jan; van de Wiel, Margje; Stolper, C. F. (Erik); Van Royen, Paul
Abstract: The role of gut feelings in diagnostic reasoning is recognized by most GPs throughout Europe, and probably throughout the world. Studies on this topic have emerged from different countries but there is the risk that authors will use different terms for similar concepts. The European Expert Group on Cognitive and Interactive Processes in Diagnosis and Management in General Practice, COGITA for short, was founded in 2008 to conduct cross-border research in the area of non-analytical diagnostic reasoning. Academic GPs, PhD students, psychologists, linguists and students meet once a year to share their experiences, exchange results and initiate new studies on the topic. A milestone in their research is this publication of a short glossary of diagnostic reasoning terms relating to the gut feelings research topic. It was constructed by the COGITA group members following a literature review, which aimed to define salient terms used in their publications. They described the terms, cross-reviewed the wording and reached consensus within the group. Two sections were created: (1) a diagnostic reasoning section that describes concepts such as analytical and non-analytical reasoning, clinical mind lines, and intuition, and (2) a research methods section describing concepts such as linguistic validity and saturation. The glossary, including relevant literature, has been published on the websitehttp://www.gutfeelingsingeneralpractice.eu . In the future, the glossary will be modified if necessary and completed by members of the COGITA group.